Conexões interfrásicas manuais e não-manuais em LGP : um estudo preliminar - Martins, Mariana (2017)
In sign language, sentence connections are not always explicit, or so easily identifiable as in spoken / written language, since these seem to be mostly undertaken by nonlexical elements. This study aims to describe the structures related to different values associated to the connector “and” in Portuguese Sign Language (Língua Gestual Portuguesa – LGP). The challenge lies in the fact that the copulative connector, besides entailing different meanings in Portuguese, does not seem to be lexicalized in LGP. Thus, we selected a set of copulative coordinate clauses with additive, temporal, inferential, contrastive and conditional values and their syntactic-semantic equivalents in Portuguese, using, in addition to “and”, other commonly used connectors (“but”, “although”, “therefore”, “after”, “if”). For each sentence in Portuguese, native speakers of LGP produced isolated translations, where it was possible to identify lexical marks, such as conjunctions (“BUT”, “THEN”, “WHILE”, “AFTER”, “AS-SOON-AS” “HOWEVER”, “IF”), adverbs, verbs and other expressions that reinforce the meaning conveyed. The analysis of these productions show that most of the sentences present prosodic connections, i.e., non-manual connectors that emerge consistently: neutral expression, frown and raised eyebrows. In LGP, lexical connectors are mostly used in the three syntactic structures that express contrast, especially in adversative coordinates (“BUT”, “HOWEVER”). On the other hand, nonmanual connectors appear mostly in asyndetic coordinates and in those connected by “and” associated to temporal and conditional values. Comparing the use of lexical and prosodic connections in LGP, it can be concluded that non-manual connectors seem to be very productive, even when there is a direct sign translation for a particular connector in Portuguese.